The most patient man - Khan , S (India , Good word books, 2012)
The story tells of a man known for his extraordinary patience. He endures insults, hardships, and difficult situations without anger or retaliation. Curious people ask him how he remains so calm. He explains that patience is a choice, a strength that grows from understanding others and not letting their negativity control your peace. His calm nature eventually earns him deep respect and admiration.